Identification of ACKR1 variants associated with altered Duffy phenotype expression in blood donors from southern Brazil. (August 2020) - Höher, Gabriela; Rodrigues, Mirelen Moura de Oliveira; Waskow, Gabriela; Agnes, Grasiela; Von Burg, Pâmela Victoria; Onsten, Tor; Fiegenbaum, Marilu; Almeida, Silvana
Abstract: The atypical chemokine receptor 1 gene (ACKR1) is responsible for the clinically significant Duffy blood group. The main antigens of this system, Fya and Fyb, can be related to a null or weak expression of the DARC protein. In the present work, we aimed to identify ACKR1 gene variants in blood donors from southern Brazil based on discrepancies between their serological and molecular typing results. Then, we analyzed the association of these variants with the expression of the Duffy phenotype. The Fy antigen types were determined via hemagglutination and real-time PCR (c.125 G > A, c.265C > T and c.−67T > C SNPs) tests in a sample composed of 382 regular repetitive voluntary blood donors to the Blood Bank of Hospital de Clínicas de Porto Alegre. An inconclusive correlation between phenotype-genotype analyses was found in 11 (2.88 %) donors, and the entire ACKR1 gene was sequenced in these samples. Our investigation found 11 genetic variants, four of which (c.−541C > T, c.21 + 150C > T, c.22−58A > G, and c.298 G > A SNPs) seem to have putative functional effects on the structure and expression of DARC undertaken for in silico analysis (SIFT, PolyPhen-2 and RegulomeDB). Molecular events can result in apparent discrepancies between red cell genotypes and phenotypes. Our findings provided insight into the molecular background of FY antigens to improve technical approaches for red cell genotyping.